2021
DOI: 10.5187/jast.2021.e46
|View full text |Cite
|
Sign up to set email alerts
|

Coping with large litters: management effects on welfare and nursing capacity of the sow

Abstract: Competing interestsNo potential conflict of interest relevant to this article was reported. Funding sourcesState funding sources (grants, funding sources, equipment, and supplies). Include name and number of grant if available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 61 publications
1
8
0
1
Order By: Relevance
“…To the knowledge of the authors, similar results have not previously been quantified. Specific benefits and drawbacks of different types of crates have recently been described by Peltoniemi et al (2021) , and are supported by results demonstrated in this study.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…To the knowledge of the authors, similar results have not previously been quantified. Specific benefits and drawbacks of different types of crates have recently been described by Peltoniemi et al (2021) , and are supported by results demonstrated in this study.…”
Section: Resultssupporting
confidence: 88%
“…Given that crate sizes have remained constant ( Goumon et al, 2022 ), this places modern sows at higher risk of poor farrowing or lactation outcomes. The main justification for using farrowing crates is to prevent the crushing of piglets by slowing sows when lying down ( Alonso-Spilsbury et al, 2007 ; Peltoniemi et al, 2021 ). At the same time, overly restrained sows can have prolonged farrowing (>4–5 h) leading to both an increased number of stillborn piglets ( Peltoniemi and Oliviero, 2015 ) and an impact on the health of sows ( Tummaruk andSang-Gassanee, 2013 ; Peltoniemi and Oliviero, 2015 ).…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, using foster sows or artificial rearing methods to improve the survival rates of small piglets from large litters may present other animal welfare problems (56). All these considerations should prompt a serious reflection on whether the persistent focus on genetic selection for large litter sizes should be reconsidered (42, 71), for instance, in favour of breeding for resilience (e.g., litter size at weaning rather than at birth), which can also respond to environmental concerns (87). In line with this, the recent Scientific Opinion on pig welfare recommends that to avoid excessive competition for access to teats in large litters, the average number of piglets born alive in a given sow breed or line should not exceed, and preferably be lower than, the average number of functional teats (75).…”
Section: The Challenge Of Large Litter Sizesmentioning
confidence: 99%
“…These changes in sow conformity and sow performance have come with challenges related to sow and piglet welfare around parturition and during lactation (reviewed by Peltoniemi et al, 2021; Rutherford et al, 2013). Farrowing large litters increases intra‐uterine competition which reduces birth weight and together with increased postnatal competition for resources (colostrum, milk) during lactation, these factors compromise postnatal survival of piglets.…”
Section: Introductionmentioning
confidence: 99%